Evaluation of The Chemical Properties, Chewiness Level, and Sensory of Yellow Pumpkin (Cucurbita moschata) Jelly Candy in Various Ratios of Caragenan and Gum Arabic - Sussi Astuti; Otik Nawansih; Sri Hidayati; Octavia Sopha Anggraini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
This study aims to determine the effect of carrageenan and gum arabic formulations on chemical properties, level of elasticity, and sensory properties of pumpkin jelly candy and to obtain the right formulation of carrageenan and gum arabic to produce good quality jelly candy. The study was arranged in a Completely Randomized Block Design with a single factor and 4 replications. The treatment was the ratio of carrageenan and gum arabic consisted of 5%:0% (K1), 4%:1% (K2), 3%:2% (K3), 2%:3% (K4), 1%:4 % (K5). The data obtained were analyzed for homogeneity with the Barlett test, ANOVA, and the Tuckey test at the 5% level.  Determination of the best treatment for pumpkin jelly candy was determined by the De Garmo method.  The results showed that the best jelly candy was the K3 treatment (3% carrageenan; 2% gum arabic) which resulted in a texture score of 3.80 (chewy), color with a score of 3.97 (dark yellow), taste with a score of 4.11 (like ), water content of 7.66%, ash content of 0.99%, reducing sugar content of 14.31%, and sucrose content of 27.7%.  Formulation of carrageenan and gum arabic significantly affected the chemical properties, level of elasticity, and sensory properties of pumpkin jelly candy. Keywords: Gum Arabic, Carrageenan, Jelly candy, Pumpkin.